2022
DOI: 10.1021/acs.est.1c06855
|View full text |Cite
|
Sign up to set email alerts
|

Gas-to-Aerosol Phase Partitioning of Atmospheric Water-Soluble Organic Compounds at a Rural Site in China: An Enhancing Effect of NH3 on SOA Formation

Abstract: Partitioning gaseous water-soluble organic compounds (WSOC) to the aerosol phase is a major formation pathway of atmospheric secondary organic aerosols (SOA). However, the fundamental mechanism of the WSOC-partitioning process remains elusive. By simultaneous measurements of both gas-phase WSOC (WSOCg) and aerosol-phase WSOC (WSOCp) and formic and acetic acids at a rural site in the Yangtze River Delta (YRD) region of China during winter 2019, we showed that WSOCg during the campaign dominantly partitioned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 54 publications
0
33
1
Order By: Relevance
“…It was also found that difference of precursors may lead to the change of WSOC in the gas-particle distribution relationship. The variation of WSOCp in Atlanta was controlled by the aerosol liquid water content (ALWC) under the influence of humidity, which was similar to WSOCp in Chongming island, China (Lv, et al, 2022). While variation of WSOCp in Los Angeles was independent of ALWC, but depended on OC concentration .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…It was also found that difference of precursors may lead to the change of WSOC in the gas-particle distribution relationship. The variation of WSOCp in Atlanta was controlled by the aerosol liquid water content (ALWC) under the influence of humidity, which was similar to WSOCp in Chongming island, China (Lv, et al, 2022). While variation of WSOCp in Los Angeles was independent of ALWC, but depended on OC concentration .…”
Section: Introductionmentioning
confidence: 67%
“…Increase of NH3 leaded to dilution of δ 13 C-WSOCp, enrichment of δ 13 C-WSOCg and increase of WSOCg on an extremely significant level (p<0.01). For there was research found increase of ALWC along with decrease of pH of aerosol in environment of high concentration of NH3 (Shaojun, et al, 2022), which may be conducive to aerosol release WSOCg. Dilution of WSOCp may came from mutual conversion of WSOCp and WSOCg, while enrichment of δ 13 C-WSOCg may came from aging of WSOCg which was generated in an environment of high concentration of NH3 considering increasing concentration of WSOCg.…”
Section: Effects Of Gaseous Pollutantsmentioning
confidence: 96%
“…The key data sets are archived at the East Asian Paleoenvironmental Science Database, National Earth System Science Data Center, National Science and Technology Infrastructure of China: https://doi.org/10.12262/IEECAS.EAPSD2022004 (Duan et al, 2022). For further information, please contact the corresponding author (rujin.huang@ieecas.cn).…”
Section: Data Availabilitymentioning
confidence: 99%
“…Numerous studies have elucidated the increasing importance of secondary aerosol in haze pollution (Sun et al, 2016;Huang et al, 2014Huang et al, , 2019An et al, 2019;Duan et al, 2021). However, the formation and evolution of secondary aerosol, especially secondary organic aerosol (SOA), is still not well understood, and this is becoming a critical concern for air pollution research (Gilardoni et al, 2016;Xu et al, 2017;Kuang et al, 2020;Zhang et al, 2021a;Li et al, 2022a;Lv et al, 2022). Deficits in the understanding of variable precursors, complex transformation, and the aging chemistry of SOA lead to insufficient knowledge of its formation as well as uncertainty in model simulations (Shrivastava et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…SO 2 also plays an important role in changing SOA formation from BVOC photooxidation and ozonolysis through sulfuric acid formation and acid-catalyzed heterogeneous reactions (Zhao et al, 2018;Xu et al, 2021). In addition, NH 3 and amines can affect the SOA yields and composition through both gas-phase and heterogeneous reactions by reacting with sulfuric or nitric acid to generate secondary inorganic aerosols (SIA) (Ma et al, 2018;Liu et al, 2021;Lv et al, 2022). However, due to complex precursors and atmospheric processes, the combined effects of anthropogenic emissions and meteorological factors on the formation of SOA are not fully understood.…”
Section: Introductionmentioning
confidence: 99%